Surveillance of antimicrobial susceptibility patterns among Stenotrophomonas maltophilia isolated in China during the 10-year period of 2005–2014. (2nd January 2018) - Hu, Li-Fen; Xu, Xi-Hai; Li, Hong-Ru; Gao, Li-Ping; Chen, Xi; Sun, Nian; Liu, Yan-Yan; Ying, Hua-Fa; Li, Jia-Bin
Abstract : The antimicrobial resistance pattern was studied among 300 Stenotrophomonas maltophilia isolates collected from 300 nonduplicated inpatients. The average age of the patients was 73.5 ± 14.6 years old. Isolates nonsusceptible to levofloxacin, chloramphenicol, minocycline or trimethoprim/sulfamethoxazole (SXT) were more prevalent in the 99 patients aged over 81 years than in the other patients ( p  < 0.05). Multidrug resistance was found to be significantly associated with isolates recovered from the blood (72.7%, p  = 0.000) and elderly patients (31.3%, p  = 0.003). A trend of increased resistance to antimicrobials and higher and higher frequencies of multidrug-resistant isolates were observed through the 10-year period, wherein the percentage of isolates resistant to SXT was significantly changed from 29.7% in 2005–2009 to 47.1% in 2010–2014 ( p  = 0.02). Clinicians are recommended to pay special attention to the possibility of multidrug-resistant S. maltophilia infection in elderly inpatients.